2022
DOI: 10.3389/fpubh.2022.850260
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization's Frontline Support to Countries During the COVID-19 Pandemic in 2020

Abstract: The World Health Organization (WHO) declared the SARS-CoV-2 outbreak a Public Health Emergency of International Concern (PHEIC) on January 30, 2020. WHO rapidly scaled up its response including through its 149 country offices to support Member States prepare for and respond to the COVID-19 pandemic. This article describes the frontline role of the WHO Country Offices (WCOs) and demonstrates that WHO utilized its existing country presence to deliver its global program of work during this unprecedented emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Another META analysis published in JAMA with 1,012 citations found that the application of systemic corticosteroids was associated with lower 28-day all-cause mortality in COVID-19 critical patients compared with routine care or placebo groups ( 50 ). Undoubtedly, since WHO declared COVID-19 as a public health emergency of international concern on January 30, 2020, which has made the most important contribution to the global fight against COVID-19: WHO rapidly scaled up its response including through its 149 country offices to support Member States prepare for and respond to the COVID-19 pandemic ( 51 ). Moreover, WHO made great efforts and contributions in many aspects such as carrying out clinical research on COVID-19 ( 49 ), developing COVID-19 vaccine and formulating international standards for antibody response of COVID-19 vaccine ( 52 , 53 ), formulating COVID-19 discharge guidelines ( 54 ) and WHO living guideline for drugs to prevent COVID-19 ( 55 ), and formulating regional and national coordination mechanisms for managing COVID-19 pandemic ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another META analysis published in JAMA with 1,012 citations found that the application of systemic corticosteroids was associated with lower 28-day all-cause mortality in COVID-19 critical patients compared with routine care or placebo groups ( 50 ). Undoubtedly, since WHO declared COVID-19 as a public health emergency of international concern on January 30, 2020, which has made the most important contribution to the global fight against COVID-19: WHO rapidly scaled up its response including through its 149 country offices to support Member States prepare for and respond to the COVID-19 pandemic ( 51 ). Moreover, WHO made great efforts and contributions in many aspects such as carrying out clinical research on COVID-19 ( 49 ), developing COVID-19 vaccine and formulating international standards for antibody response of COVID-19 vaccine ( 52 , 53 ), formulating COVID-19 discharge guidelines ( 54 ) and WHO living guideline for drugs to prevent COVID-19 ( 55 ), and formulating regional and national coordination mechanisms for managing COVID-19 pandemic ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are being made worldwide to prevent and reduce the incidence of COviD-19 [12]. the restrictions and lockdowns in many countries have had a considerable impact on the mental state of the entire population, particularly young people [13], and some authors have described it as the largest psychological experiment conducted to date [14]. while transmission, symptom occurrence and mortality rates are lower among young people, they have been more severely affected by the strict measures necessary to limit the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…During COVID-19, the WHO provides frontier support in leadership, policy dialogue and strategic support, as well as technical assistance and service delivery [ 12 ]. After the Wuhan Municipal Health Commission reported the cluster of atypical pneumonia cases, the WHO set up the Incident Management Support Team on January 1, 2020, to deal with the outbreak.…”
Section: Introductionmentioning
confidence: 99%